2011
DOI: 10.1371/journal.pone.0020771
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptomic Analysis of Intestinal Tissue to Assess the Impact of Nutrition and a Secondary Nematode Challenge in Lactating Rats

Abstract: BackgroundGastrointestinal nematode infection is a major challenge to the health and welfare of mammals. Although mammals eventually acquire immunity to nematodes, this breaks down around parturition, which renders periparturient mammals susceptible to re-infection and an infection source for their offspring. Nutrient supplementation reduces the extent of periparturient parasitism, but the underlying mechanisms remain unclear. Here, we use a genome wide approach to assess the effects of protein supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
(88 reference statements)
3
9
0
Order By: Relevance
“…Consistent with this observation is our recent finding that the satiety peptide ghrelin is also differentially expressed between the resistant and susceptible sheep, even in the nematode naïve sheep [39]. In another study, genes associated with the expulsion of nematodes were also shown to be regulated by nutritional status [40]. The network developed from the susceptible animal is quite different and is arranged around the cytokines IL4 and IFNγ, although these cytokines were not themselves identified in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this observation is our recent finding that the satiety peptide ghrelin is also differentially expressed between the resistant and susceptible sheep, even in the nematode naïve sheep [39]. In another study, genes associated with the expulsion of nematodes were also shown to be regulated by nutritional status [40]. The network developed from the susceptible animal is quite different and is arranged around the cytokines IL4 and IFNγ, although these cytokines were not themselves identified in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Four weeks after the secondary challenge, DUOX2 expression had continued to increase, while DUOXA2 expression had plateaued. These results have recently been supported by studies from other research groups who found a rapid escalation in both DUOX2 and DUOXA2 gene expression in the small intestine of cattle infected with Cooperia oncophora (Li and Gasbarre, 2009), and similarly elevation of DUOX2 in the small intestine of mice infected with Nippostrongylus brasiliensis (Athanasiadou et al, 2011).…”
Section: Introductionsupporting
confidence: 68%
“…In our chronic infection model, loss of active DUOX enzymes led to increased mucosal colonization and exacerbated, yet futile, chronic inflammatory response. The subunits of the DUOX2 isoenzyme have been identified among the highest induced genes in Crohn’s disease 11,12 , irritable bowel syndrome 13 , and infectious diseases 14,47 . It remains to be shown whether loss of DUOX activity will also exacerbate other infectious or chronic inflammatory conditions of the luminal GI tract in which DUOX was found to be activated.…”
Section: Discussionmentioning
confidence: 99%